Effect of Mastery Learning Model Implementation on Student Learning Outcomes at Darussalam Islamic Middle School - Nur Aisyah; Hastuti Agussalim; Nursamsi Nursamsi; Sukmawati Sukmawati; Indahwaty Indahwaty (International Journal of Mathematics and Science Education, 2025)
This study aims to examine the influence of the implementation of the Mastery Learning model on the study results of seventh-grade students at Darussalam Islamic Middle School, Gowa. This research is a type of classroom action research (CAR), designed to improve the mathematics learning outcomes of seventh-grade students. The CAR approach was implemented in a cyclical form, consisting of four stages: (1) planning, (2) action, (3) observation, and (4) reflection. Data collection techniques used in this study included observation, testing, and documentation. Data analysis was carried out using descriptive analysis to assess both the learning outcomes and the teacher and student activities during the process. The results of the first and second cycles indicate a significant improvement in student performance. In the first cycle, the study results showed a 75% improvement in student learning outcomes, and after the second cycle, student performance improved to 90%. The class's average grade also increased significantly, from 71 in the first cycle to 87 in the second cycle. This improvement demonstrates that the implementation of the Mastery Learning model can significantly enhance the mathematics learning outcomes of seventh-grade students at Darussalam Islamic Middle School, Gowa. Furthermore, this study proves that the collaborative approach in classroom action research not only improves student learning outcomes but also fosters an engaging and effective learning environment. The results suggest that the Mastery Learning model, with its emphasis on achieving mastery in learning before progressing to the next topic, is an effective strategy for improving mathematics achievement in middle school students. This study contributes valuable insights into the effectiveness of the Mastery Learning model in enhancing student performance in mathematics.